Deciphering antiviral efficacy of malaria box compounds against malaria exacerbating viral pathogens- Epstein Barr virus and SARS-CoV-2, an in silico study - Omkar Indari; Ajit Kumar Singh; Deeksha Tiwari; Hem Chandra Jha; Anupam Nath Jha (Elsevier, 2022)
In malaria endemic countries, coinfections and cotransmissions of different viral pathogens are widely reported. Prior studies have shown that malaria can trigger the Epstein-Barr virus (EBV) reactivation in the body. Besides, the altered immunity due to malaria could increase susceptibility to acquire co-circulating viruses like SARS-CoV-2 or vice versa during pandemic times. The dual burden of pathogens can deteriorate health by inducing disease severity. There are no or limited antiviral therapies available against EBV and SARS-CoV-2. Exploring the novel antimalarials for checking antiviral efficacy and using them in such cases could be the efficient approach of 'hitting two birds with one stone'. We investigated the antiviral potency of medicine for a malaria venture's malaria box containing 400 drug-like or probe-like compounds with experimentally proven antimalarial activity. We utilized a molecular docking approach to screen these compounds against crucial proteins- EBNA1 of EBV and RdRp of SARS-CoV-2 respectively. Based on binding affinity we shortlisted the top three compounds for each protein. Further, for validation of complex stability and binding, the protein-ligand complex is subjected to 100 ns molecular dynamic simulation. All the compounds showed stable binding with respective proteins. Based on binding free energies, involvement of important residues from target sites, and ADMET properties of compounds, the top ligand for each protein is selected. Ligand B (MMV665879) for EBNA1 (ΔGbind = -183.54 kJ/mol) and Ligand E (MMV665918) for RdRp (ΔGbind = -172.23 kJ/mol) could act as potential potent inhibitors. These antimalarial compounds can hence be utilized for further experimental investigation as antivirals against EBV and SARS-CoV-2.